Nyugat felé félúton (Szociológiai Szemle, 2024)
According to the results of our survey conducted on a national 1000-member representative sample there are still people in a significant majority whose views and attitudes related to the goals of the society, to the optimum organisation of the economy, to market competition, to the role of the state, the rights and duties of the individual are more or less resolutely and consistently opposed to some such im portant liberal values and principles, to latent social strategies which play a fundamental role in the organisation and operation of the advanced societies of the West. The anti-liberal, paternalistic, anti-Western attitude is so strong and general that it makes hardly any difference among the groups identified by the basic demographic-social characteristics: the anti-Western views and attitudes are present essentially in an almost similarly great proportion in every group. The difference among people and their groups is caused not so much by the anti-Western, but much more by the acceptance of the Western views and attitudes. A basic anti-Western tuning can be traced even in those groups - such as men. the younger generations, the highly qualified, people living in urbanised settlements and among the better off - where otherwise the pro-Western attitudes, by and large weaker and more limited, are the strongest. The socio-economic attractions of the sympathisers of parties show a sim ilar image too: even among the supporters of those parties, such as SZDSZ, Fidesz and MSZP, among the followers of which the pro-Western attitude is relatively the strongest, there is a marked non-Western value choice.As if the impression, many times worded in many places, were being justified that there are several parties hidden in some of the Hungarian parties. According to our survey at least two of them: a smaller but markedly pro-Western and a more populous but mixed and non-Western one are there. Quite probably this conflict of values has played a significant role in the MDNP breaking away from the MDF and in the split of KDNP, further on in a number of internal disputes in the coalition of the MSZP and SZDSZ.